Discussion of “Combining Health Data Uses to Ignite Health System Learning” - Denaxas, S.; Friedman, C. P.; Geissbuhler, A.; Hemingway, H.; Kalra, D.; Kimura, M.; Kuhn, K. A.; Payne, H. A.; de Quiros, F. G. B.; Wyatt, J. C. (Methods of Information in Medicine, 2015)
This article is part of a For-Discussion-Section of Methods of Information in Medicine about the paper “Combining Health Data Uses to Ignite Health System Learning” written by John D. Ainsworth and Iain E. Buchan [1]. It is introduced by an editorial. This article contains the combined commentaries invited to independently comment on the paper of Ainsworth and Buchan. In subsequent issues the discussion can continue through letters to the editor.With these comments on the paper “Combining Health Data Uses to Ignite Health System Learning”, written by John D. Ainsworth and Iain E. Buchan [1], the journal seeks to stimulate a broad discussion on new ways for combining data sources for the reuse of health data in order to identify new opportunities for health system learning. An international group of experts has been invited by the editor of Methods to comment on this paper. Each of the invited commentaries forms one section of this paper.
Keywords: Health data reuse; secondary uses; meaningful use; learning health systems; adaptive health systems; intelligence pipelines; health-care evidence; population health